Kehadiran Gereja dalam Kemajemukan Indonesia dalam Terang Yes 49:6 dan Mat 28:19 - Grets Janialdi Apner (P3TK, Sanata Dharma University, 2018)
This article proposes a reconstruction contextual theology of mission for Indonesian-Christian with comparative-hermeneutical method on Isaiah 49:6 and Mathew 28:19. It is true that theology of mission in Christianity has been growth in theory. However, its not the reality of Christian practical life, especially in Indonesia, who keep doing Christianization as their mission. They are still believe that the indicator to done a mission are make other people to be a Christian. The Great Commission in Matthew 28:19 is used as the biblical foundation to do the Christianization. It is a way of doing theology that should be reconstructed to produce a practical mission which suitable in context of Indonesia. This writing will give a reconstruction on Matthew 28:19 that will be compared to Isaiah 49:6. The aim of this comparison is to build a wider landscape and more open perspective for Indonesian-Christian to presence in Indonesia civil society. It is a way of doing mission as a Christian and an Indonesian at the same time who cares about the plurality of Indonesias context.